Analysis of the Influence of ROA, ROE and NPM in Predicting Profit Growth in the Agricultural Industry Listed on the IDX (Year 2020-2023) - Sri Yulia; Maya Syaula; Kasim Siyo (Yayasan Multidimensi Kreatif, 2024)
This research aims to analyze the influence of return on assets, return on equity and net profit margin on profit growth in the Agricultural Industry listed on the IDX. The sample used in this research is based on predetermined criteria, the number of agricultural sector companies listed on the Indonesia Stock Exchange in 2020 - 2023 that have met the criteria in sampling is 9 companies. The number of years of observation used in this research is 4 years so the number of observations in this research is 36 observation sample units. The results of the partial analysis show that the t-value is 7.959 > 2.03 (t-table) and sig 0.000 < 0.05, so H1 is accepted and H0 is rejected, it can be concluded that return on assets has a significant effect on profit growth. The t-calculated value is 0.792 < 2.03 (t-table) and sig 0.434 < 0.05, so H2 is rejected and H0 is accepted, it can be concluded that return on equity has no significant effect on the company's profit growth. The t-calculated value is 0.702 < 2.03 (t-table) and sig 0.488 > 0.05, so H3 is rejected and H0 is accepted, it can be concluded that the net interset margin has no significant effect on profit growth. The calculated F value of 24.391 is greater than the F table which is 3.24 with a significance level of 0.000 which is much smaller than 0.05, so it can be concluded that hypothesis H4 is accepted which means return on assets, return on equity and net interest margin have a significant effect simultaneously. on profit growth.